Cluster Analysis of New Students at STKIP Pembangunan Indonesia during the COVID-19 Pandemic Based on Regional Origin - Isma Muthahharah; Sutamrin; Khadijah (PT ARRUS Intelektual Indonesia, 2023)
This study aims to determine the distribution of origins of prospective new STKIP Pembangunan Indonesia students during the COVID-19 pandemic based on the student's name, religion adopted, chosen study program, and sources of information on new student admissions. The method used is clustering with a total sample of 27 regions in Indonesia. In this study, 3 clusters were formed, namely cluster 1 which had the most students with members namely East Jakarta, East Kalimantan, Gowa, Maros, Takalar, Bantaeng, Manggarai, West Manggarai, East Flores, West Sumba. Cluster 2 has not too many (moderate) prospective students with members namely Makassar, Barru, SInjai, Bulukumba, Soppeng, Enrekang, Jeneponto, Selayar, Polewali Mandar, East Maggarai. Cluster 3 has the fewest prospective students with members namely Makassar, Barru, Sinjai, Bulukumba, Soppeng, Enrekang, Jeneponto, Selayar, Polewali Mandar, East Maggarai